Headache among combat-exposed veterans and service members and its relation to mild traumatic brain injury history and other factors: a LIMBIC-CENC study - Walker, William C.; Clark, Sarah W.; Eppich, Kaleb; Wilde, Elisabeth A.; Martin, Aaron M.; Allen, Chelsea M.; Cortez, Melissa M.; Pugh, Mary Jo; Walton, Samuel R.; Kenney, Kimbra (Frontiers in Neurology, 2023)
The association between Headache (HA) and remote mild traumatic brain injury (mTBI) is not well established, and risk factors are understudied. We demonstrated that HA is extremely common among formerly combatexposed military personnel and that their remote mTBI history is associated with elevated odds of HA. Blastrelated mTBIs were uniquely associated with a higher degree of HA impact on daily life. This was shown in both bivariate analyses and multivariable regression adjusting for numerous sociodemographic, health, and symptom measuresincluding PTSD. These findings highlight the ramifications of mTBI in the military population, and will inform clinical screening, education, and monitoring strategies. Clinical strategies to provide early or targeted intervention should also incorporate the other risk factors we identified among our covariates including female sex, Black racial identity, Hispanic/Latino ethnicity, and younger age. Modifiable treatment targets we identified include PTSD, depression, and sleep quality.